Pengaruh Penambahan Jenis Gula yang Berbeda Terhadap Karakteristik Fisikokimia dan Organoleptik Yoghurt Nanas - Suciati, Fitri; Ratnasari, Uneng; Fathurohman, Ferdi; Ramadhan, Muhammad Gilang; Purwasih, Rita (BPFP Universitas Bengkulu, 2022)
Yogurt is a fermented milk beverage, in general fruit added to yoghurt to improve it taste. Pineapple added to improve taste of yoghurt, aside pineapple addition, sugar added to balance sweet and sour taste of yoghurt. Sugar type have different characteristic. The aim of this research to observe the effect of sugar type on physicochemical and organoleptic pineapple yoghurt. This research used Completely Randomized Design (CRD) with 3 treatments, namely granulated white sugar (P1), granulated palm sugar (P2) and granulated coconut sugar (P3) with 3 replications. Parameters observed were physical characteristic (color), chemical characteristics (pH and Total Soluble Solid (TSS)) and organoleptic (hedonic test). The color were analyzed descriptively, pH and TSS were evaluated using ANOVA and differences between the treatments were analyzed using Duncan Multiple Range Test (DMRT) with α=0,05 significance level, whereas the result of hedonic test (flavour, aroma, color and texture) were analyzed descriptively using mode. The color of pineapple yoghurt with the addition of various type of sugar were cloudy brown (P1) and sandrift brown (P2 and P3). The addition of sugar type had a significant effect (P<0.05) on pH, however had no significant effect (P>0,05) on TSS. The pineapple yoghurt with granulated white sugar (P1) had most attributed in the like category in taste, aroma and texture with pH value 3,79 and TSS 23 oBrix. Key words: Granulated Coconut Sugar, Granulated Sugar, Granulated Palm Sugar, Pineapple, and Yoghurt ABSTRAK Penelitian ini bertujuan untuk mengevaluasi profil darah ayam broiler yang diberi ekstrak daun kitolod (Isotoma longiflora) melalui air minum. Penelitian ini menggunakan 200 ekor ayam broiler dengan 5 perlakuan dan 4 ulangan. P0: Air minum + 0% ekstrak daun kitolod, P1: Air minum + tetracyclin, P2: Air minum + 1,5% ekstrak daun kitolod, P3:Air minum + 3,0% ekstrak daun kitolod, P4: Air minum + 4,5% ekstrak daun kitolod. Rancangan yang digunakan dalam penelitian ini adalah rancangan RAL (Rancangan Acak Lengkap), dianalisis dengan menggunakan ANOVA. Variabel yang diamati yaitu sel darah merah (eritrosit), hemoglobin, sel darah putih (leukosit), hematokrit. Hasil penelitian ini menunjukkan bahwa perlakuan tidak berpengaruh nyata (P>0,05) terhadap sel darah merah (eritrosit), hemoglobin, sel darah putih (leukosit), hematokrit. Sel darah merah (eritrosit) berkisar antara 2,10-2,52 × 106µl, hemoglobin berkisar antara 9,8-11,1 g/dL, sel darah putih (leukosit) berkisar antara 175,8-183,7 × 103µl, dan hematokrit berkisar 28,8-32,5 %. Kesimpulan dari penelitian ini pemberian ekstrak daun kitolod (Isotoma longiflora) dari perlakuan 1,5% - 4,5% dapat mempertahankan profil darah ayam broiler.